2018
DOI: 10.3389/fpsyg.2018.01858
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Based Guided Imagery as an Intervention for State Anxiety

Abstract: Anxiety is a significant mental health issue in modern society and empirical research into effective interventions to address anxiety has been extensive. Spending time in nature is one approach that has demonstrated anxiolytic effects. However, in some situations and contexts spending time in nature in order to reduce anxiety symptoms may not be possible. For example, in therapeutic settings delivered in a space with no access or exposure to any nature stimuli in the immediate surrounding environment. Guided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 57 publications
(97 reference statements)
1
45
0
5
Order By: Relevance
“…When comparing indoor to outdoor PA, people who exercise outdoors reported decreased feelings of tension, confusion, anger, and depression [25]. Research has indicated that exposure to nature increases positive psychological health outcomes such as happiness, mood, and self-esteem; furthermore, it enhances vitality, and reduces stress [26]. Therefore, older adults who stayed at home were able to spend significantly more time on housework and light exercise/sports; in addition, outdoor activities such as walking and gardening may have contributed to the maintenance of SWB scores.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing indoor to outdoor PA, people who exercise outdoors reported decreased feelings of tension, confusion, anger, and depression [25]. Research has indicated that exposure to nature increases positive psychological health outcomes such as happiness, mood, and self-esteem; furthermore, it enhances vitality, and reduces stress [26]. Therefore, older adults who stayed at home were able to spend significantly more time on housework and light exercise/sports; in addition, outdoor activities such as walking and gardening may have contributed to the maintenance of SWB scores.…”
Section: Discussionmentioning
confidence: 99%
“…Exercising outdoors and in sight of nature has additional benefits for our relationship with the natural world by reducing anxiety (Bratman et al., 2015; Hyvönen et al., 2018; Lawton et al., 2017; Niedermeier, Hartl, & Kopp, 2017; Wooller, Barton, Gladwell, & Micklewright, 2016). Even virtual reality interactions can have a positive impact for those with limited access to nature (Calogiuri et al., 2018; Nguyen & Brymer, 2018).…”
Section: Urban Ecosystems In the Global Biodiversity Crisis And In Edmentioning
confidence: 99%
“…Interestingly, the perceptual hierarchy in PCT can short-circuit the exterm environment and enter an imagination mode whereby stored perceptions are experienced “as if” real to the brain (Powers, 1973 ). This capacity has been used to explain the role of imagery in psychological interventions (e.g., Mansell and Hodson, 2009 ), and there is evidence that mental imagery of natural scenes may be particularly beneficial, for example in reducing state anxiety (Nguyen and Brymer, 2018 ).…”
Section: Discussionmentioning
confidence: 99%